Simulation Study on the Performance of Kevlar Fibre Reinforced Composites Under the Penetration of Fragment. Issue 1 (March 2021) - Li, Shuhu; Wang, Ronghui; Zhang, Dashun; Du, Juan; Xu, Jingli; Zhang, Haiyun; Liu, Fangbiao
Abstract: Aiming at the problem of Kevlar fibre reinforced composite target anti penetration of wedge-shaped fragment, the finite element models of Kevlar fibre reinforced composite targets with different thickness and the fragments are established. The simulation calculation of Kevlar fibre reinforced composite target against penetration of different velocity fragments is carried out. The anti-ballistic V50 of Kevlar fibre reinforced composite target with different thickness is obtained, and the damage failure mode of the Kevlar fibre reinforced composite target in the process of anti fragment penetration is analyzed, and the simulation results are verified by experiments. This simulation provides scientific basis and data support for the optimization design of composite structure armor and armor lining.